Companion encyclopedia of the history of medicine - Bynum, W. F. (William F.), 1943-; Porter, Roy, 1946-2002 (Routledge reference., 1993)
This text provides an account of the development of medical science in its various branches, and includes discussions of the medical profession and its institutions, and the impact of medicine upon populations, economic development, culture, religions, and thought.